2021
DOI: 10.1108/lht-07-2020-0180
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to accept social robots in museums: an exploratory factor analysis according to visitor profile

Abstract: PurposeThe aim of this exploratory study is to identify the factors that influence the acceptance of social robots in museum environments and determine if this influence depends on the visitor's profile (age, gender, education and occupation).Design/methodology/approachData collected from an electronic questionnaire include 433 responses from Spanish visitors. The authors subjected the variables proposed by De Kervenoael et al. (2020) adapted to museums. The initial descriptive analysis only showed significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…The roundtable guide considered previous studies, and it was divided into three blocks: (1) the functionality of AI (Pinillos et al, 2016;Wu and Cheng, 2018;Wirtz et al, 2018;Ivanov et al, 2018;Tussyadiah and Park, 2018;Ivanov et al, 2019;Li et al, 2021), (2) the contact of AI with users (Primawati, 2018;Tussyadiah and Park, 2018;Gaia et al, 2019;Fuentes-Moraleda et al, 2021) and (3) the co-experience dimension of AI (Heerink et al, 2010;Van Doorn et al, 2017;Stock and Merkle, 2018).…”
Section: Roundtable Discussion' Guide and Organisationmentioning
confidence: 99%
See 1 more Smart Citation
“…The roundtable guide considered previous studies, and it was divided into three blocks: (1) the functionality of AI (Pinillos et al, 2016;Wu and Cheng, 2018;Wirtz et al, 2018;Ivanov et al, 2018;Tussyadiah and Park, 2018;Ivanov et al, 2019;Li et al, 2021), (2) the contact of AI with users (Primawati, 2018;Tussyadiah and Park, 2018;Gaia et al, 2019;Fuentes-Moraleda et al, 2021) and (3) the co-experience dimension of AI (Heerink et al, 2010;Van Doorn et al, 2017;Stock and Merkle, 2018).…”
Section: Roundtable Discussion' Guide and Organisationmentioning
confidence: 99%
“…The literature review reveals that no study has investigated visitors' and managers' perceptions of AI applications in museums and cultural organisations from the 5.0 perspective. Recent research approaches AI implementation in cultural organisations (museums) from the users' perspectives and a quantitative prism (Webster and Ivanov, 2022;Fuentes-Moraleda et al, 2021). Industry 5.0 is a new concept, and there is little literature around it.…”
Section: Introductionmentioning
confidence: 99%
“…Hsu and Liang (2022) developed a universal game-based blended museum learning service and showed that it engaged museum visitors and promoted their return visits. Readers may also be interested in reading our earlier articles on the use of virtual reality in museums to engage users (Lo et al , 2019) and social robots in museums (Fuentes-Moraleda et al , 2022).…”
Section: Using Contemporary Technologies In Cultural Services Venuesmentioning
confidence: 99%
“…Edwards et al (2022) discussed the relationship between self-reported levels of acute stress, perceived social support and interactions with robot animals in an academic library. Fuentes-Moraleda et al (2022) presented an exploratory study of a multidimensional instrument for measuring willingness to accept social robots in museum contexts. Tung and Campos (2022) introduced a social robot app called the Music Buddy that can play situational music based on users' electroencephalogram data.…”
Section: Prefacementioning
confidence: 99%